The role of financial literacy in retirement planning: A mini review - Yahaya, Rusliza; Husin, Azrizal; Borhan, Nur Amirah (International Journal of Accounting, Finance and Business, 2025)
This mini-review synthesizes recent evidence on the role of financial literacy in retirement planning, focusing on how it shapes planning strategies, financial behaviour, and core competencies such as budgeting, saving, investing, and debt management. Using Scopus and Google Scholar, a literature search conducted on 12 September 2025 identified peer-reviewed studies addressing financial literacy and retirement preparedness. The findings reveal that financial literacy interventions enhance savings behaviour, reduce financial stress, and improve retirement readiness, particularly when implemented through early education, workplace initiatives, and digital tools like robo-advisors, gamified applications, and retirement calculators. However, persistent issues remain, including unequal access to financial education, socioeconomic disparities, cultural influences, and doubts about the sufficiency of literacy alone to change behaviour without supportive policy frameworks. Debates also continue regarding the causal relationship between financial literacy and behavioural outcomes, as well as the long-term impact and ethical concerns associated with digital finance solutions. Major gaps identified include limited longitudinal studies, inconsistent measurement of financial literacy, and insufficient assessment of intervention cost-effectiveness. Overall, financial literacy is essential but not independently sufficient for sustainable retirement preparedness. Strengthening its impact requires integration with behavioural and policy mechanisms. Future research should emphasize longitudinal and cross-cultural studies on blended financial education and technology-based interventions, prioritize equity-focused programs for vulnerable populations, and establish ethical standards for AI-driven financial tools to ensure inclusive and resilient retirement security.